Depositing Ag2S quantum dots as electron mediators in SnS2/g-C3N4 nanosheet composites for constructing Z-scheme heterojunction with enhanced photocatalytic performance. (January 2021) - Fan, Zhongwei; Luan, Jingfei; Zhu, Changqing; Liu, Fuqiang
Graphical abstract: Highlights: A novel Z-scheme system of g-C3 N4 /Ag2 S/SnS2 with Ag2 S quantum dots as electron mediators Synthesis the photocatalyst by in-situ ion exchange and self-peeling Photodegradation of methyl orange and phenol under visible light irradiation Superoxide radicals and holes were the main photocatalytic active species The probable photocatalytic mechanism was proposed combined various tests Abstract: The novel Z-scheme heterojunction photocatalyst g-C3 N4 /Ag2 S/SnS2 with Ag2 S quantum dots as electron mediators was successfully synthesized by in-situ ion exchange reaction and self-peeling of g-C3 N4 . Compared with g-C3 N4, SnS2 or g-C3 N4 /SnS2, the photocatalyst g-C3 N4 /Ag2 S/SnS2 exhibited more excellent photocatalytic performance under visible light irradiation. The removal rate of methyl orange was 96.8% after 30 minutes visible light irradiation and the reaction rate constant reached 0.10225 min -1 . The enhanced photocatalytic activity could be attributed to the formation of Z-scheme heterojunction structure and the 2D layered structure. The electrochemical and photoelectric performance tests showed that the separation and transfer efficiency of the photogenic electron-hole pairs as well as the redox potential were significantly improved. Additionally, the quenching experiments showed that the superoxide radicals and holes were the primarily active species. Combined with other characterizations, the reaction mechanism of the g-C3 N4 /Ag2 S/SnS2 for degrading the target pollutant methyl orange under visible light irradiation was proposed.